Culture shift : transforming your church from the inside out - Lewis, Robert, 1949 Nov. 24-; Bird, Warren; Cordeiro, Wayne (San Francisco, CA : Jossey-Bass, 2005)
"Culture Shift, written for church leaders, ministers, pastors, ministry teams, and lay leaders, leads you through the process of identifying your church's distinctive culture, gives you practical tools to change it from the inside-out, and provides steps to keep your new culture aligned with your church's mission. Real transformation is not abut working harder at what you're already doing or even copying another church's approach but about changing church culture at a foundational level."--BOOK JACKET.
Foreword / Erwin Raphael McManus -- PART 1. Awakening to culture: 1. Why culture matters -- 2. Your destiny in seed form -- 3. What you think is what you see -- PART 2. Birthing the culture: 4. Totems : identifying your church's culture -- 5. How to shift your church's culture -- 6. Divine partnership -- PART 3. Growing the culture at New Hope O'ahu: 7. Identifying New Hope's totems -- 8. Culture setters -- 9. Plug-and-play subculture vs. authentic culture -- 10. Creating and re-creating culture -- PART 4. Growing the culture at Fellowship Bible Church: 11. Identifying Fellowship Bible's totems -- 12. The power of a disciplined vision -- 13. Learning to spot opportunity -- 14. Courageous adjustments to safeguard the values -- PART 5. Advancing the culture: 15. Irresistible culture -- Appendix 1. Involvement and satisfaction survey -- Appendix 2. Sample pages from a Life Journal.
Includes bibliographical references (p. 205-207) and index.
Keywords: Church renewal; Christianity and culture